(3aVd GdLdO, YfO abO GdhdOs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg Ydi cd MGd gPG JCdja dWja aj eG hQO aj ehJ GdChdGO SejJg ajg CMGOjK hBKGQ hfNH hMcGjGJ hGYJHGQ hgh KGdK eDda CdaJg aj gPG GdHGH PcQ GdBjI GdcQjeI GdhGQOI aj Pdc bGd Gddg JYGdis
(3BNQgG (B:s
(3hbGd hCfTOfG CHh YKeGf bGd CfTOfG GdJhRj dHYV GdTYQGA Whi GdehJ eG Hjfj hHjf eMeO hdjS deG JWhj GdefjI fGTQ dFf ChMTJ eef CMH efGRd dbO CfSJ eef CMH GdebGHQ hcfJ Ydjg CMPQ GdehJ hMOg JeJs
(3Vef eLehY Hg QSGdI HNW eWGHb eDQNI (B1124 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\301s
(3cTa GdXfhf (B2\1278s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdJUha hGdBOGH GdTQYjIs